Lower IGF-1 and Alkaline Phosphatase Activity Blood Levels in Stunted Children with Soil-Transmitted Helminth Infections - Tiara Mayang Pratiwi Lio; Heri Wibowo; Mohamad Sadikin; Sri Widia A. Jusman (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Stunting due to malnutrition and soil-transmitted helminth (STH) chronic infections can cause disturbances in bone formation processes during growth. Reduced levels of insulin-like growth factor 1 (IGF-1) lead to reduced osteoblast activity which can be monitored through alkaline phosphatase (ALP) and osteocalcin (OCN). Unfortunately, studies that assessed IGF-1, OCN, and ALP together in stunted children with STH infection are still limited. Therefore, in this study, the osteoblast activity was monitored by measuring IGF-1, OCN, and ALP in stunted and normo-stature children with STH infection.METHODS: A case-control study involving 28 stunted and 33 normal-stature children was conducted. Blood plasma IGF-1 and OCN levels were measured using the enzyme linked immunosorbent assay (ELISA) method, while ALP activity was measured using the colorimetric method. STH infection was examined by direct smear method. The parameters were analyzed and compared between the stunted and normo-stature children.RESULTS: Although in stunted boys there was no significant difference, however in stunted girls with positive STH infection, a decrease in IGF-1 (<36.60 ng/mL vs. ≥36.60 ng/mL) showed an impact on the decrease of OCN levels (54.68 (42.22-144.54) ng/mL vs. 104.55 (86.14-392.73) ng/mL; p=0.047). ALP activity in children with positive STH infection showed that ALP activity in stunted children was lower than in normo-stature children (18 (10-671) U/L vs. 228.50 (16-574) U/L; p=0.005).CONCLUSION: The blood levels of IGF-1 and ALP activity in stunted and positive STH infected children tend to be lower than in normo-stature children.KEYWORDS: stunted, normo-stature, IGF-1, bone alkaline phosphatase, osteocalcin